Strategi Anggota DPRD Provinsi NTT Dalam Memenangkan Pemilu Legislatuf 2024 (Kemenangan Simprosa Rianasari Gandut di Dapil 4 Kabupaten Manggarai) - Charlyn M. I. D. Ndoen; Rex Tiran; Diana S. A. N. Tabun (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
This study analyzes the winning strategy of Simprosa Rianasari Gandut in the 2024-2029 Legislative Election in Manggarai Regency Dapil 4. Although Simprosa Rianasari Gandut is a newcomer to political contestation, she managed to get the most votes and beat the incumbent from the same party. The study employs a qualitative approach with descriptive analysis, emphasizing interviews, literature review, and direct observation of Simprosa Rianasari Gandut’s political activities. This research uses a qualitative method with a descriptive approach to explore the strategies applied, including push marketing (direct and face-to-face campaigns with the public), pull marketing (utilization of print and social media to build a political image), and pass marketing (involving traditional leaders and social networks to strengthen support). In addition, this research also identifies the supporting and inhibiting factors for its success, such as the support of family, success teams, political parties, as well as the challenges of patriarchal culture. The results show that a direct communication-based approach, active involvement in the community, and an effective political marketing strategy were key to Simprosa Rianasari Gandut’s victory. These findings provide insights into the dynamics of electoral politics, especially for female legislative candidates who want to compete in a political system that is still dominated by men.